3D Guided Implant Surgery: A Case Report - Maharjan, Shyam K.; Mathema, S.R.B.; Shrestha, S.M. (Journal of Nepalese Prosthodontic Society, 2018)
Dental implant has been established as one of the most predictable and conservative approaches for the rehabilitation of missing teeth. With the evolution of newer material and advancement in digital technology, specially in computed tomography, implant planning software and guided implant surgery, the outcome and success in implant dentistry has become more predictable. Computer aided design (CAD) technique is being integrated into treatment planning, and computer-assisted manufacturing (CAM) is becoming more popular for rehabilitation procedures. This case report illustrate the diagnosis, planning and application of 3D guided technology in dental implant surgery